2022
DOI: 10.21834/ebpj.v7i21.3692
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Entrepreneurs and Environmental Sustainability: Millennials in Malaysia

Abstract: The advantage of today's millennials is that the amount of information at their fingertips is almost unlimited. They may be particularly capable of looking for opportunities in the new economic environment of the era of epidemics. However, the study on social media's influence on the development of entrepreneurial skills among millennials has received little attention thus far. In addressing this gap, this study explores the influence of social media as perceived entrepreneurial skills learned by millennials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, previous research has not explained the relationship between social media marketing activities and satisfaction (Chen and Lin, 2019). Furthermore, the findings of previous studies still focus on BRIC countries and ignore technological and economic changes in developing countries (Kiss et al, 2012;Grzeslo, 2020), so that information concludes that the use of social media has an essential and reliable role in improving performance business is still limited (Othman et al, 2022). It should be remembered that every developing country has unique conditions and differences in cultural, economic, technological and infrastructure aspects.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, previous research has not explained the relationship between social media marketing activities and satisfaction (Chen and Lin, 2019). Furthermore, the findings of previous studies still focus on BRIC countries and ignore technological and economic changes in developing countries (Kiss et al, 2012;Grzeslo, 2020), so that information concludes that the use of social media has an essential and reliable role in improving performance business is still limited (Othman et al, 2022). It should be remembered that every developing country has unique conditions and differences in cultural, economic, technological and infrastructure aspects.…”
Section: Introductionmentioning
confidence: 96%
“…Several previous studies have concluded that the use of marketing strategies through social media can be trusted and proven to increase business creativity, satisfaction and performance of entrepreneurs (Rialp-Criado and Rialp-Criado, 2018;Tajvidi and Karami, 2021;Othman et al, 2022). However, previous research has not explained the relationship between social media marketing activities and satisfaction (Chen and Lin, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations